Recontextualizing the Dynamics of Kembar Buncing Custom In the Bali Aga Villages of Buleleng - Rustiani, Komang Wahyu; Suarka, I Nyoman; Darma Putra, I Nyoman; Suraya, Rahmat Sewa; Resen, Putu Titah Kawitri (Jayapangus Press, 2025)
This study explores the evolving perception of the kembar buncing custom among the Bali Aga community, where the birth of unlike sex twins was traditionally considered a taboo, believed to bring misfortune and resulting in social stigma, exile, and financial burdens for affected families. In recent years, however, the perception has shifted toward greater inclusivity, with such births increasingly viewed as symbolic representations of harmony between good and evil. The study aims to understand the dynamics of this cultural transformation and its broader implications for preserving Bali Aga identity amid the pressures of modernity. Using a qualitative approach, data were collected through observation, non-participatory interviews, document analysis, and focus group discussions (FGDs). The analysis followed the Miles and Huberman model, involving data reduction, data display, and verification to ensure systematic interpretation. The theoretical framework is informed by Pierre Bourdieu’s theory of habitus, which provides tools for analyzing how social dispositions evolve through interactions with structural forces and through the strategic use of various forms of capital: economic, social, cultural, and symbolic. The findings reveal that the transformation of the kembar buncing custom is driven by regulatory adaptation, cultural negotiation, hegemonic resistance, and symbolic reconstruction. Changes in community habitus, shaped by the strategic mobilization of capital by key social actors, have contributed to a shift in customary paradigms. This transformation suggests the need to recontextualize traditional customs within contemporary frameworks, not only to ensure cultural sustainability but also to advance human rights and social inclusion within the Bali Aga society.